Real convergence, the European Community and Ireland - Kennedy, Kieran A. (Statistical and Social Inquiry Society of Ireland, 1992)
As is well known, average living standards in Ireland are much lower than in most of our EC partners. It is of considerable interest to Ireland whether, and in what way, its living standards will catch up or fall further behind as Europe becomes more integrated. The issue is understandably at the heart of the government's strategy towards the EC, and was at the forefront of its diplomatic efforts to secure assurances on economic and social cohesion at the Maastricht summit last December. The issue has also been the subject of a number of valuable studies (see especially Bradley et al., 1992; NESC, 1989; O'Donnell, 1991). Yet I believe that we need to think a great deal more about this issue, both at the levels of analysis and of policy. My address will have served its purpose if it gives an impetus to such thinking.
Read before the Society, 14 May 1992
Keywords: Economic convergence; Living standards; 314.15